2012
DOI: 10.1103/physrevb.86.085409
|View full text |Cite
|
Sign up to set email alerts
|

Probing the experimental phonon dispersion of graphene using12C and13C isotopes

Abstract: Using very uniform large-scale chemical vapor deposition grown graphene transferred onto silicon, we were able to identify 15 distinct Raman lines associated with graphene monolayers. This was possible thanks to a combination of different carbon isotopes and different Raman laser energies and extensive averaging without increasing the laser power. This allowed us to obtain a detailed experimental phonon dispersion relation for many points in the Brillouin zone. We further identified a D + D peak corresponding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 24 publications
5
72
0
Order By: Relevance
“…The focus of this work is to understand the effect of isotopic substitution on the position and linewidth of the main Raman features (D, G, G * , and 2D bands). The analysis of the 2D Raman peak as a function of the 13 C concentration and laser energy allowed us to conclude that the slopes of the electronic and phonon dispersions near the K point are not affected by the isotope enrichment of the graphene samples. Finally, we present results of the phonon mean free path as a function of the isotopic ratio.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The focus of this work is to understand the effect of isotopic substitution on the position and linewidth of the main Raman features (D, G, G * , and 2D bands). The analysis of the 2D Raman peak as a function of the 13 C concentration and laser energy allowed us to conclude that the slopes of the electronic and phonon dispersions near the K point are not affected by the isotope enrichment of the graphene samples. Finally, we present results of the phonon mean free path as a function of the isotopic ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have suggested that the G band resonance is closely related to the optically allowed electronic transition in twisted bilayer graphene [18,19]. Bernard et al [13] identified several weak Raman peaks in isotope-enriched graphene, ascribed to the double-resonance Raman process, and obtained phonon dispersion for these mixed isotopic materials [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations